Clinical trials roundup in idiopathic inflammatory myopathies - Mann, Heřman F; Vencovský, Jiří (Current opinion in rheumatology, 2011)
PURPOSE OF REVIEW: To review recent advances in the treatment of idiopathic inflammatory myopathies (IIMs) with emphasis on new biological agents and on some less commonly used immunosuppressive drugs. RECENT FINDINGS: Double-blinded comparison of oral high-dose pulse dexamethasone with standard high daily prednisolone doses showed similar efficacy in the composite score, significantly longer median time to relapse with prednisolone and fewer side effects with dexamethasone treatment. Use of intravenous immunoglobulins (IVIGs) in IIMs is associated with variable results; however, recent retrospective evaluation of IVIGs administration to steroid-resistant patients with esophageal involvement showed good effect. Whereas smaller open studies with rituximab reported a very good efficacy, even in notoriously difficult-to-treat anti-signal recognition particle-positive cases, the double-blind trial has not reached the primary endpoint. Studies with TNF neutralization are reporting results ranging from only a modest or no effect to a promising outcome in the most recent trial with etanercept. Pilot studies suggest efficacy of alemtuzumab in inclusion body myositis and allogeneic mesenchymal stem cell transplantation in polymyositis/dermatomyositis. SUMMARY: Unmet need for efficacious therapy in IIMs exists and therefore a coordinated effort is necessary to properly evaluate various new classical and biological agents.
Keywords: klinické zkoušky jako téma; rituximab; Humans; lidé; Tumor Necrosis Factor-alpha; imunosupresiva; protilátky nádorové; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; intravenózní imunoglobuliny; myozitida; dermatomyozitida; Myositis; Clinical Trials as Topic; TNF-alfa; Rituximab; Antibodies, Neoplasm; Interleukin 1 Receptor Antagonist Protein; antagonista receptoru pro interleukin 1; transplantace mezenchymálních kmenových buněk; Dermatomyositis; Glucocorticoids; alemtuzumab; Immunosuppressive Agents; glukokortikoidy; Immunoglobulins, Intravenous; Antibodies, Monoclonal, Murine-Derived; myší monoklonální protilátky; Alemtuzumab; Mesenchymal Stem Cell Transplantation